Verbal cognitive processing and emotion regulation among indigenous Sami children - YLIRANTA, AINO (2010)
The study investigated the impact of cultural changes on children's cognitive and socioemotional development. Research among Arctic indigenous populations suggests that their ancient lifestyles and living environments have caused the development of a specific cognitive profile featured by strong simultaneous, as opposed to successive, style of information processing. Futhermore, Greenfield's model of social change and child development suggests that the sociodemographic features of children's living environments affect the way their self-regulative abilities emerge. These propositions were tested among indigenous Sami children. It was hypothesized that the Sami children would show (1) superior simultaneous processing skills together with lower general verbal ability and successive processing ability as well as (2) better emotion regulation ability compared to their non-indigenous peers. Additionally, the association of cognitive processing tendencies and emotion regulation was investigated. Seven-year-old Sami children and their Finnish and Norwegian peers (N = 52) were assessed with selected subtests of the NEPSY Developmental Neuropsychological Assessment and the Wechsler Intelligence Scale for Children - Third Edition (WISC-III) as well as with parental ratings of emotion regulation capacity. The Sami children's general verbal ability was in part poorer than that of the non-indigenous group. The Sami did not show any specific tendency to simultaneous information processing nor better emotion regulation ability. Strong successive processing was found to correlate positively to paternal ratings of emotion regulation and negatively to maternal ratings. The results suggest that the cultural transition toward Nordic majority societies has diminished or eradicated the specific cognitive and socioemotional features of the indigenous Sami. It is proposed that the development of emotion regulation may owe more to implicit learning than to verbal communication within the social environment.